KEPEMIMPINAN KEWIRAUSAHAAN KEPALA SEKOLAH DALAM MENGEMBANGKAN SEKOLAH DI SMK KESEHATAN HAJI SUMATERA UTARA - Suhendra, Budi; Elfrianto, Elfrianto; Isman, Muhammad (EDUTECH, 2024)
This research aims to find out the entrepreneurial leadership of school principals is in developing schools at the SMK Kesehatan Haji Sumatera Utara, This research uses a descriptive qualitative approach, data collection is carried out using interview, observation, and documentation techniques, the data analysis technique used in this research is collection. Data, data reduction and drawing conclusions. The results of the research show that: 1) The principal of the SMK Kesehatan Haji Sumatera Utara has entrepreneurial leadership competencies in carrying out his duties, namely leading with the characteristics of an entrepreneur, being brave in making decisions, having a work team, accepting ideas and opinions, having the courage to take and assess risks, having a partner. work, open thinking and high self-confidence. 2) The principal's entrepreneurial leadership is able to develop the school in the graduate aspect, namely creating academic assistant teachers to help students who want to work, continue higher education and entrepreneurship, 3) The principal's entrepreneurial leadership is able to develop the school in the curriculum aspect, namely the school creates Nine Featured Curriculum Aspects ( SAKU) as a guide for carrying out learning activities 4) The school principal's entrepreneurial leadership is able to develop the school in terms of facilities and infrastructure, namely by utilizing technology to carry out efficiency and develop creative products by utilizing all existing potential and assets, 5) The school principal's entrepreneurial leadership able to develop the school in the aspect of building partnerships, namely that the principal collaborates with various government and private agencies to improve the school and establish cooperation for students who want to work in Japan